Study on the academic future of second-generation immigrants in Setubal and Faro (Portugal) - Vicente J. Llorent; Vicente Llorent-Bedmar; José-Manue (Sociedad Iberoamericana de Pedagogía Social, 2015)
The research focuses on the Luso-African secondary school pupils studying in two of the Portuguese cities with the largest number of immigrants (Setúbal and Faro). Especially this cities, according to the latest data offered in Portugal by the National Institute of Statistics, in the near future these young people constitute the majority of the school population in many schools in the country and at the same time, a large portion of them will help to raise and high rates of dropout and failure. In order to facilitate the social inclusion of these students wanted to determine their expectations of their school career, taking into account social, family, economic, educational and school aspects. After a relevant documentary study, we conducted a data collection based on the in situ observation and a vertebrate of questionnaire scales in seven groups: characteristics of their parents, school career, self-esteem, motivation to continue studying, expectations about the future professional, characterization and evaluation of the school context, and expectations after high school. Thus, variables relate concerning their social and family situation, your school career and social integration with their future prospects. Following the interpretation and analysis of the extracted data, among other findings, we argue that the most influential in the expectations of the Luso- African students who complete their secondary education factor is the interest of parents in the education of children In order to facilitate the inclusion of socio students involved in migration processes, we aim to determine their expectations about their school. Especially because, according to latest data provided by the National Institute of Statistics in Portugal, in the near future these young people constitute the majority of the school population in many centers in that country and at the same time, much of it will help raise the actual high dropout and failure rates. Through our research we gather information from all the Luso-African secondary schools in two cities with the largest number of Portuguese immigrants (Setúbal and Faro). Data collection was performed using a questionnaire developed, aimed at the students of Portuguese-speaking Africa and was divided into seven major groups of scales: characteristics of parents, school career, self-motivation to continue studying, professional expectations about the future, characterization and evaluation of the school setting, and characterization of expectations after secondary school. The extracted data includes social, familial, economic, educational and school children of immigrants, called second-generation immigrants or Luso-Africans. Thus, we find relations between their prospects and their social and family situation variables that influence school and their school and their social integration. After interpretation and analysis of extracted data, we conclude that the most influential factor in expectations, with the Luso-African students who complete their secondary school studies, is the interest of the parents regarding the formation of the children.